Textile design - Clarke, Simon (Laurence King, 2011)
Textile design has a very exciting future. New fibres, fabrics and applications are constantly appearing and designers now have a wealth of avenues to explore. This book offers students a basic grounding in the three main pathways of textile design printed, woven and mixed media textile design.